1999
DOI: 10.1038/sj.sc.3100887
|View full text |Cite
|
Sign up to set email alerts
|

Training of the respiratory muscles in individuals with tetraplegia

Abstract: Study design: An experimental cross-sectional design. Objectives: To evaluate whether training of the innervated respiratory muscles in individuals with a (partial) cervical spinal cord injury will improve the strength and endurance capacity of these muscles and the exercise performance in these individuals. Setting: Department of Physiology and Pulmonary diseases, Nijmegen, The Netherlands. Method: In this study nine individuals with tetraplegia (C3 ± C7) performed a target¯ow endurance training of the inspir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 22 publications
2
52
0
3
Order By: Relevance
“…(1,8) Several studies have demonstrated that the inspiratory muscles of quadriplegic patients can be trained by increasing MIP, inspiratory muscle endurance, lung volume and capacity. (6,(8)(9)(10)(11)(12)(13)(14)(15)(16) Those studies have used different methods for overloading inspiratory muscles, such as the use of threshold trainers, resistive trainers or abdominal weights, as well as normocapnic hyperpnea and training protocols involving high or unknown loads. (11)(12)(13) Some studies have included a control group, (2,11,16,17) whereas others have included only a training group or compared the type of training used with that of another protocol.…”
Section: Methodsmentioning
confidence: 99%
“…(1,8) Several studies have demonstrated that the inspiratory muscles of quadriplegic patients can be trained by increasing MIP, inspiratory muscle endurance, lung volume and capacity. (6,(8)(9)(10)(11)(12)(13)(14)(15)(16) Those studies have used different methods for overloading inspiratory muscles, such as the use of threshold trainers, resistive trainers or abdominal weights, as well as normocapnic hyperpnea and training protocols involving high or unknown loads. (11)(12)(13) Some studies have included a control group, (2,11,16,17) whereas others have included only a training group or compared the type of training used with that of another protocol.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 The most important pulmonary function change is a nonparenchymatous pulmonary restriction, 4,5 owing to weakness or paralysis of respiratory muscles. 6,7 Maximal static mouth respiratory pressures are used in the evaluation of respiratory muscle strength. 8 Studies in patients with spinal cord lesions are infrequent, but point to a reduction over wide range in these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies in people with CSCI show that RMT can improve ventilatory function. 139,140 In a review article of Van Houtte et al 141 they reported that RMT tended to improve expiratory muscle strength, VC and RV.…”
Section: Resultsmentioning
confidence: 99%